Adverse reactions to metal on polyethylene implants: Highly destructive lesions related to elevated concentration of cobalt and chromium in synovial fluid. Issue 7 (29th March 2017) - Eltit, Felipe; Assiri, Ali; Garbuz, Donald; Duncan, Clive; Masri, Bassam; Greidanus, Nelson; Bell, Robert; Sharma, Manju; Cox, Michael; Wang, Rizhi
Abstract: Adverse local tissue reactions (ALTR) are the primary cause of failure of metal on metal (MoM) hip implants, and fewer but not negligible number cases of nonmodular metal on polyethylene (MoP) implants. In this study, we analyzed 17 cases of MoP ALTR, and equal number of MoM, by histological observation, cobalt and chromium concentration in serum and synovial fluid and cytokine analysis in ALTR tissues. ALTRs in MoP are highly necrotic, affecting larger areas than MoM ALTRs. Degenerative changes in blood vessels' wall were seen in all MoP ALTRs. The concentration of cobalt and chromium was higher in synovial fluid but lower in serum of MoP patients compared to MoM patients. Elevated concentrations of chemokines were observed in ALTR tissues. We conclude that ALTRs in MoP systems are highly necrotizing lesions that seem to have a similar development to ALTRs in MoM. Alteration of vessels wall seems to have a role in the tissues necrosis, as well as the elevated concentration of cobalt and chromium in synovial fluid of MoP patients. Chemokines may be involved in the pathogenesis of ALTR and constitute possible diagnostic targets. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1876–1886, 2017.